HUBUNGAN KECERDASAN EMOSI DENGAN KOMPETENSI KEPRIBADIAN GURU se-KECAMATAN LUBUK DALAM - Fauziah, Hayatul; Indarto, Wusono; ', Nurlita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This study aims to determine the relationship between emotional intelligence competencies early childhood teacher personality as the District Lubuk In. Quantitative correlation study type approach. Data research on emotional intelligence that is obtained through a questionnaire statement amounted to 30 items, and personal competence as early childhood teachers in districts Lubuk obtained through a questionnaire of 20 items. Furthermore, researchers disseminate research questionnaires to sample as many as 30 samples which had been set to obtain research data. To reveal the emotional intelligence obtained from the questionnaire with 30 items statement, as well as personal competence early childhood teachers as districts Lubuk In the diebarkan the study sample were 30 with a score for each answer was given a score of 4 strongly agree, agree was given a score 3, do not agree given a score of 2, strongly disagree was given a score of 1. Levels relationship between emotional intelligence and personal competence as a teacher in the District Lubuk in middle category is 0.599. Thus the hypothesis proposed in this study that there is a relationship between sounds and emotional intelligence and personal competence as early childhood teachers in the District Lubuk acceptable.Keywords: Emotional Intelligence, Personality Teacher Competence